Introduction to Helicopter and Tiltrotor Flight Simulation, Second Edition - Dreier, Mark E. (American Institute of Aeronautics and Astronautics, 2018)
This book brings the tools required to write a flight simulation mathematical model together in one comprehensive reference. Twenty-two chapters comprise the main body of the text. Each chapter builds on the lessons of the previous chapter and lays the foundation for the chapter. The appendices supply the building material. Dedicated chapters on the aerodynamics and dynamics of fuselages, wings, propellers, rotors, landing gear, engines, drive trains, controls, and aerodynamic interference precede the final chapters on overall organization, information flow, and trimming methods. Fourteen appendices provide important reviews of numerical and analytical techniques in the calculus, linear algebra, rotor basics, Biot-Savart law, momentum theory, units, and humorous axioms about flight. The text supports the lessons with many examples, 400 illustrations, a problem set, and a series of over 40 demonstration programs that "bring the equations to life." The text can be used for senior-level and graduate-level instruction and as a reference for the practicing engineer. The text presents the material in an accessible, fun, and easy-to-understand style, yet "carefully and completely (a rarity!) develops the mathematics for modeling rotary wing aerodynamics."-- Provided by publisher.
Keywords: Helicopters -- Aerodynamics -- Computer simulation.; Helicopter flight simulators.; Tilt rotor aircraft -- Computer simulation.; elektronické knihy; electronic books